Problem-Based Learning dan Pengaruhnya Terhadap Penguasaan Konsep Biologi: Studi Eksperimen di Sekolah Berbasis Pondok Pesantren - Ibana, Lukluk; Antika, Linda Tri; Fathir, Akhmad; Rofiqi, Rofiqi (Indo-MathEdu Intellectuals Journal, 2025)
Biology education at the secondary school level plays a crucial role in shaping students' understanding of scientific concepts related to life. One of the main challenges in biology learning is the low level of students’ conceptual understanding, which can impact their critical thinking and problem-solving abilities. This study aims to examine the effect of the Problem-Based Learning (PBL) model on students' understanding of biology concepts. The subjects of the study were students from class X-A Science and X-B Science at MA Miftahul Ulum Nagasari Congkop Tlambah, Karang Penang, Sampang, during the second semester of the 2022/2023 academic year. This research employed a quantitative approach with a quasi-experimental design, specifically using the non-equivalent pretest-posttest control group design. The instruments used are the Student Worksheet (LKPD), test devices (pretest and posttest), and observation sheets for the implementation of PBL syntax. The data analysis used is inferential statistics with parametric statistical techniques. Students’ conceptual understanding of biology was measured using a scoring rubric based on the revised Bloom’s Taxonomy by Anderson & Krathwohl, integrated into a written test. Data analysis was conducted using Quade’s Rank test with the help of SPSS version 28.00. The results showed that the PBL model had a significant effect on students' understanding of biology concepts, with an effect size of 0.299.